Investigating the Differential Effects of Early Child Care and Education in Reducing Gender and Racial Academic Achievement Gaps From Kindergarten to 8th Grade - Dong, Nianbo; Bulus, Metin; Curenton, Stephanie M.; Ibekwe-Okafor, Nneka (Journal of Education, 2024)
We used the generalized propensity score method to estimate the differential effects of five Early Child Care and Education (ECCE) experiences (Prekindergarten, Head Start, Center-based Child Care, Home-based Child Care, and Parental Care) in reducing math and reading achievement gaps between boys versus girls, Latinx versus Whites, and Blacks versus Whites. Findings revealed differential effects of ECCE in reducing gender and racial achievement gaps. However, results indicated that significant gender and racial gaps still exist despite ECCE experiences and that these gaps widen throughout the elementary and middle school years.
Keywords: Differential Effects; Early Care and Childhood Education; Generalized Propensity Score; Academic Achievement Gaps